Pedagogies of plurality : education, cultural resilience, and well-being in indigenous Chiapas : a thesis presented in fulfilment of the requirements for the Master of International Development, School of People, Environment and Planning, Massey University - Brockliss, Joseph TJ (Massey University, 2025)
Indigenous communities in Chiapas, Mexico, have faced centuries of exclusion through colonialism, state assimilation policies, and global economic inequalities. Education has often served as a tool of this exclusion, undermining Indigenous languages, knowledge systems, and communal ways of life. In 1994, the Zapatista movement declared autonomy and began establishing its own schools as part of a broader struggle for dignity, self-determination, and justice for the Indigenous communities of Chiapas. This inspired other Indigenous communities in Chiapas to establish their own schools with a similar focus on autonomy and cultural preservation. These autonomous schools reject the logic of Western development, re-centring education within Indigenous knowledge, communal decision-making, and traditional cultural practices. This thesis explores how the Indigenous autonomous education movement of Chiapas contributes to social well-being when understood through the lens of buen vivir, a framework that recognises the interdependence of social, cultural, ecological, and spiritual life. Drawing on desk-based research and semi-structured interviews with individuals associated with the Zapatista movement and connected Indigenous communities, this study examines how education in Chiapas fosters five key areas: language, identity, and cultural resilience; environmental awareness, agriculture, and food sovereignty; social and physical infrastructure; educational sovereignty and intellectual liberation; and collective ethics. The findings reveal that well-being does not arise from isolated schooling initiatives but from embedding education into the social fabric of the community and resisting external models that compartmentalise daily life. While challenges remain, such as funding shortages, cultural tensions, and ongoing pressures from State aggression, organised crime, and globalisation, the Zapatistas and other Indigenous communities of Chiapas exemplify how Indigenous-led education can generate resilience, cultural strength, and collective dignity. This study demonstrates that education, when reimagined from below, can become a practice of resistance and renewal, contributing to a broader vision of post-development grounded in Indigenous autonomy and hope.
Copyright holders of any copyrighted images are invited to use the Take Down Request link below to request their removal.
Keywords: 390203 Sociology of education; 451904 Global Indigenous studies peoples, society and community